Diagnosing Organizational Identity Beliefs by Eliciting Complex, Multimodal Metaphors. (December 2013) - Jacobs, Claus D.; Oliver, David; Heracleous, Loizos
The purpose of this article is to extend the organizational development diagnostics repertoire by advancing an approach that surfaces organizational identity beliefs through the elicitation of complex, multimodal metaphors by organizational members. We illustrate the use of such "Type IV" metaphors in a postmerger context, in which individuals sought to make sense of the implications of the merger process for the identity of their organization. This approach contributes to both constructive and discursive new organizational development approaches; and offers a multimodal way of researching organizational identity that goes beyond the dominant, mainly textual modality.